Multiple Polar and Non‐polar Nematic Phases - Brown, Stevie; Cruickshank, Ewan; Storey, John M. D.; Imrie, Corrie T.; Pociecha, Damian; Majewska, Magdalena; Makal, Anna; Gorecka, Ewa (Chemphyschem, 2021)
Liquid‐crystal materials exhibiting up to three nematic phases are reported. Dielectric response measurements show that while the lower temperature nematic phase has ferroelectric order and the highest temperature nematic phase is apolar, the intermediate phase has local antiferroelectric order. The modification of the molecular structure by increasing the number of lateral fluorine substituents leads to one of the materials showing a direct isotropic‐ferronematic phase transition. Liquid‐crystal materials exhibiting polar nematic phases and having a dielectric permittivity of the order of 104 are reported. An intermediate phase formed between the ferroelectric and non‐polar nematic phases has antiferroelectric order. Lateral substitution of the mesogenic core with fluorine atoms decreases the shape anisotropy and in turn stabilizes the polar ferroelectric phase. For one of the studied materials, a direct Iso‐NF transition is found.